Towards a metric for Open Source Software Quality - Shaikh, Siraj; Cerone, Antonio (Electronic Communications of the EASST, 2009)
Software quality is more than just conformance to a set of requirements and represents many attributes related to each other that make up a piece of software. An important part of this measure depends on the underlying processes and methodologies used in the engineering of software. We present an early exposition towards a quality model for open source software (OSS). We describe some basic notions of quality for OSS and present a basic model, where quality notions consist of various factors that influence such quality. The purpose of this effort is ultimately to develop a quantitative metric for software quality.